2016
DOI: 10.1055/s-0042-118228
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal arteriovenous malformation: endosonographic diagnosis and coil embolization

Abstract: with Doppler evaluation is a good imaging modality for characterizing vascular lesions involving the wall of the gastrointestinal tract [5]. Bleeding from duodenal AVMs is extremely rare. This case is unique because of the characteristic appearance of the AVM on endoscopic ultrasound and the successful management by angioembolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Poon et al 3 reported a duodenal AVM in a 47‐year‐old man with melena which was initially misdiagnosed as a varix due to its appearance and the patient's history of alcoholism; the bleeding recurred after Histoacryl injection, and an AVM was diagnosed by angiography; surgical intervention was performed after embolization due to persistent melena and shock. Endoscopic ultrasonography and angiography may assist diagnosis, while angiography provides a vascular map that is essential for planning management 3,5 . AVMs are characterized by a large afferent artery, a racemose vascular network, and early venous drainage, as revealed by angiography in our case.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Poon et al 3 reported a duodenal AVM in a 47‐year‐old man with melena which was initially misdiagnosed as a varix due to its appearance and the patient's history of alcoholism; the bleeding recurred after Histoacryl injection, and an AVM was diagnosed by angiography; surgical intervention was performed after embolization due to persistent melena and shock. Endoscopic ultrasonography and angiography may assist diagnosis, while angiography provides a vascular map that is essential for planning management 3,5 . AVMs are characterized by a large afferent artery, a racemose vascular network, and early venous drainage, as revealed by angiography in our case.…”
Section: Discussionmentioning
confidence: 69%
“…These treatments are less likely to be successful for large submucosal vessels; thus, surgical intervention is the mainstay of treatment 2–4 . However, treatment with endoscopic and angiographic methods seems to be acceptable in selected cases 5,6 . In our case, TAE was initially successful, but bleeding recurred 8 months later due to large and abundant blood vessels supplying the AVM.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Table 1 shows reported cases of small intestinal AVM (18 cases) [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. Age of onset is wide-ranging (19 months to 95-years).…”
Section: Discussionmentioning
confidence: 99%
“…The patient has since not reported any further bleeding episodes and has remained stable with no requirement for iron infusions during a 10month follow-up period. Large duodenal AVMs are rare and previous case reports have described successful management of bleeding lesions with angiographic embolization [1,2] although this approach has not been universally effective [3], nor has laparoscopic ligation of the feeding branch of the gastroduodenal artery [3]. Band ligation has not been previously described but carries the risk of delayed bleeding from post-ligation ulcer development and glue injection has only provided temporary hemostasis in another case report [3].…”
mentioning
confidence: 99%